The handbook of communication and corporate reputation - Carroll, Craig E. (Handbooks in communication and media ;, 2013)
"With the latest insights from the world of communication studies into the nature of corporate reputation, this new addition to Wiley-Blackwell's series of handbooks on communication and media reflects the growing visibility of large businesses' ethical profiles, and tracks the benefits that positive public attitudes can bring. Serves as the definitive research collection for a fast-growing field featuring contributions by key international scholars Brings together state-of-the-art communication studies insights on corporate reputation Identifies and addresses the lacunae in the research literature Applies new theoretical frameworks to corporate reputation "--